Cryolipolysis for Submental Fat Reduction: A Systematic Review and Meta-Analysis - Do, Kenny; Ghani, Nabih; Lloyd, Nathan; Sagalow, Emily S.; Young, Kurtis; Tam, Benjamin; Tian, Sisi; Ching, Harry H.; Bigcas, Jo-Lawrence (Facial Plastic Surgery, 2025)
Submental fat can be addressed using both surgical and nonsurgical techniques. Cryolipolysis is a noninvasive treatment that uses cold temperatures to trigger apoptosis in adipose tissue.This study aims to evaluate the efficacy and safety of cryolipolysis for submental fat reduction, specifically analyzing changes in submental fat thickness and volume. It is hypothesized that cryolipolysis leads to measurable improvements in submental fat among patients.This is a systematic review and meta-analysis conducted in accordance with the PRISMA reporting guidelines.A literature search was performed across PubMed, Scopus, and Web of Science from 1973 to 2025. A total of 951 articles were screened, and eight pre-post studies involving 206 patients met inclusion criteria.Pooled analysis showed a mean reduction in submental fat thickness of −2.78 mm and volume of −19.57 cm3.Cryolipolysis significantly reduces submental fat with minimal, transient side effects.
Keywords: cryolipolysis; submental fat reduction; facial plastics; surgery; otolaryngology; noninvasive fat reduction